PEMBAGIAN URUSAN PEMERINTAHAN ANTARA PEMERINTAH PROVINSI DENGAN PEMERINTAH KABUPATEN/KOTA DALAM BINGKAI OTONOMI DAERAH - Hana Faridah (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2018)
The authority of the Regional Government is the distribution of power from the central government to the regions where the regions are given the authority to manage and regulate policies for the region. Besides, local governments also have the authority to issue regional regulations in which these regulations are used to regulate the running of government in the area. Based on Law Number 32 of 2004, the implementation of regional autonomy is focused on the provincial and district/city governments. The research method used is normative juridical research with the consideration that the starting point of research analysis of the laws and regulations Act Number 23 of 2014 concerning Regional Government. The results of this study are to find out and analyze the arrangements and mechanisms for the division of government affairs between the central government, provincial governments and district/city governments before and after the enactment of Law Number 23 of 2014 concerning Regional Government. Prior to the enactment of Law Number 23 of 2014 concerning Regional Government, the implementation of regional autonomy in terms of the division of government affairs between provincial and district/city governments in the period of enactment of Law Number 1 of 1945 concerning Regional National Committees up to Law Number 5 of 1974 concerning the Principles of Regional Government, it is still not clearly regulated what matters are the affairs of government, other than that in Law Number 5 of 1974 which emphasizes regional autonomy to the district/city government does not run as it should.